Chromatin structure and transposable elements in organismal aging - Wood, Jason G.; Helfand, Stephen L. (Frontiers in Genetics, 2013)
Epigenetic regulatory mechanisms are increasingly appreciated as central to a diverse array of biological processes, including aging. An association between heterochromatic silencing and longevity has long been recognized in yeast, and in more recent years evidence has accumulated of age-related chromatin changes in C. elegans, Drosophila, and mouse model systems, as well as in the tissue culture-based replicative senescence model of cell aging. In addition, a number of studies have linked expression of transposable elements (TEs), as well as changes in the RNAi pathways that cells use to combat TEs, to the aging process. This review summarizes the recent evidence linking chromatin structure and function to aging, with a particular focus on the relationship of heterochromatin structure to organismal aging.